We are More Than Your Paycheck: The Dehumanization of International Students in the United States - Castiello-Gutiérrez , Santiago; Li, Xiaojie (Journal of International Students, 2020)
International students in the U.S. have been pushed out and dehumanized by the policies of the Trump Administration. While sometimes the arguments used to defend the importance of international students tend to perpetuate their commodification; the rapid, coordinated, and powerful mobilization led by scholars and higher education institutions after the #StudentBan, gives us hope for a more inclusive future.